Integrated SDGs in PBL with Ethnocomics Rempong Damar to Stimulate Students' Critical Thinking Skills and Sustainability Awareness - Maulina, Dina; Abdurrahman, Abdurrahman; Nurhanurawati, Nurhanurawati; Meriza, Nadya; Fathimah, Ismah; Priadi, Median Agus; Balqis, Balqis; Ibrahim, Nor Hasniza (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2026)
This study explores how SDGs-integrated Problem-Based Learning (PBL), supported by Repong Damar ethno-comics, contributes to the development of students’ critical thinking and sustainability awareness. A quasi-experimental approach with a non-equivalent control group design was applied to two tenth-grade classes at Senior High School Perintis Bandar Lampung selected purposively. Students’ critical thinking was assessed using essay tests, while sustainability awareness was measured through questionnaires. The findings revealed a statistically significant difference between groups (p < 0.05). The experimental class demonstrated a higher N-gain (0.64, moderate) compared to the control class (0.47, moderate). In addition, sustainability awareness in the experimental group reached a high category (85.8%). These results highlight the potential of combining SDGs-oriented PBL with culturally relevant media to create meaningful learning experiences that support both cognitive and sustainability-related competencies. Integrasi SDGs dalam Problem-Based Learning Berbantuan Etnokomik: Pengaruhnya terhadap Keterampilan Berpikir Kritis dan Kesadaran Keberlanjutan Siswa ABSTRAK: Penelitian ini mengkaji peran pembelajaran Problem-Based Learning (PBL) terintegrasi SDGs yang didukung etno-komik Repong Damar dalam mengembangkan keterampilan berpikir kritis dan kesadaran keberlanjutan siswa. Metode yang digunakan adalah kuasi eksperimen dengan desain non-equivalent control group pada dua kelas X SMA Perintis Bandar Lampung yang dipilih secara purposive. Data keterampilan berpikir kritis diperoleh melalui tes esai, sedangkan kesadaran keberlanjutan diukur menggunakan angket. Hasil penelitian menunjukkan adanya perbedaan signifikan antara kedua kelompok (p < 0,05). Kelompok eksperimen memiliki nilai N-gain lebih tinggi (0,64, kategori sedang) dibandingkan kelompok kontrol (0,47, kategori sedang). Selain itu, tingkat kesadaran keberlanjutan pada kelompok eksperimen berada pada kategori tinggi (85,8%). Temuan ini menunjukkan bahwa integrasi PBL berbasis SDGs dengan media kontekstual berbasis budaya lokal mampu memberikan pengalaman belajar yang bermakna serta mendukung pengembangan kemampuan kognitif dan kesadaran keberlanjutan siswa.